2007
DOI: 10.1253/circj.71.1610
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Pulmonary Toxicity in Japanese Patients Receiving Low-Dose Amiodarone

Abstract: Background Amiodarone-induced pulmonary toxicity (APT) is the most serious side-effect of amiodarone, and its detection and prevention are extremely important. This study was designed to evaluate the incidence and clinical risk factors of APT, and the utility of a pulmonary function test or serum KL-6 assay to predict pulmonary toxicity in Japanese patients receiving low-dose amiodarone. Methods and ResultsFive hundred consecutive patients receiving amiodarone were retrospectively evaluated. Mean follow-up per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 33 publications
2
51
1
1
Order By: Relevance
“…3 Higher daily doses are associated with a greater incidence of pulmonary toxicity but may occur in patients taking lower doses (Յ200 mg/d). [6][7][8] Amiodarone and its metabolite desethylamiodarone are cationic amphiphilics that accumulate in organs with high lipid content, including the lungs. 5 Both can be toxic to lung tissue even at therapeutic serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…3 Higher daily doses are associated with a greater incidence of pulmonary toxicity but may occur in patients taking lower doses (Յ200 mg/d). [6][7][8] Amiodarone and its metabolite desethylamiodarone are cationic amphiphilics that accumulate in organs with high lipid content, including the lungs. 5 Both can be toxic to lung tissue even at therapeutic serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…34,35) The incidence of amiodarone-induced pulmonary toxicity was recently reported to be 2.1% per year in 500 Japanese patients on low maintenance doses of less than 200 mg daily, 36) which is not low compared with the 1.8% per year in a meta-analysis of 6,500 American and European patients in placebo-controlled amiodarone trials. 37) Other studies in small numbers of Japanese patients with atrial tachycardia found that 2.7-3.6% of patients receiving amiodarone developed pulmonary toxicity during mean follow-up periods of 30-36 months.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to be difficult to administer amiodarone to patients randomly as the first-choice drug for paroxysmal AF in routine practice in Japan because pulmonary toxic effects such as interstitial pneumonia occur at an incidence of about 2.1% yearly. 36) Secondly, recurrence of AF was diagnosed at the time of detection of AF on ECG. A study using ambulatory 24-hour monitoring reported that more than half of tachycardic episodes were not recognized by patients with paroxysmal AF who had obvious symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…AIPT increases 3-fold for every 10 years of age in patients aged >60 years compared to those aged <60 years. Patients receiving a daily dose greater than 400 mg/day are at higher risk compared to those receiving 200 mg/ day [10,11]. Moreover, a study among Japanese patients demonstrated that the incidence of AIPT increased from 4.2% to 7.8% and 10.6% with 1.3 years and 5 years use of amiodarone respectively, with a mean maintenance dose of 141 mg daily.…”
Section: Case Reportmentioning
confidence: 99%